On-skin ultrathin and stretchable multifunctional sensor for smart healthcare wearables - Zhang, Shipeng; Chhetry, Ashok; Zahed, Md. Abu; Sharma, Sudeep; Park, Chani; Yoon, Sanghyuk; Park, Jae Y. (Npj flexible electronics, 2022)
The flexible and stretchable multifunctional sensors for the precise monitoring of the human physiological health indicators is an emerging requirement of next-generation electronics. However, the integration of multifunctional sensors into a common substrate for simultaneous detection of such signals without interfering with each other is the most challenging work. Here, we propose MXene-Ti 3 C 2 T x and 3, 4-ethylene dioxythiophene (EDOT) deposited on laser-induced graphene (LIG/MXene-Ti 3 C 2 T x @EDOT) composite-based flexible and stretchable multifunctional sensors for strain, temperature, and electrocardiogram (ECG) monitoring. In-situ electrophoretic deposition (EPD) of MXene-Ti 3 C 2 T x @EDOT composite into LIG outperforms high strain sensitivity of 2,075, temperature coefficient of resistance (TCR) of 0.86%, and low skin-contact impedance. The sensor platform is integrated into an ultrathin and highly resilient polystyrene- block -poly(ethylene- ran -butylene)- block -polystyrene (SEBS). Finally, we demonstrate on-site detection of human body-induced deformations and physiological health indicators, such as temperature and ECG. The proposed approach paves a promising route to future wearables for smart skin and healthcare applications.